Diffuse Coronary Artery DiseaseScope of PCI in the Era of Drug Eluting Stent, A single center experience - Sohail, Khondker Mahbub; Momenuzzaman, NAM; Begum, Fatema; Shafique, Abu Md; Khan, Kaiser Nasrullah; Adhikary, Dipal Krishna; Haque, AK Fazlul (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2013)
Background: Treatment of focal or short length coronary lesions with drug eluting stents has low rate of target vessel revascularization and other major adverse cardiac events. However, safety and efficacy use of overlapping drug-eluting stents with diffuse coronary artery lesions is debatable and we do not have much experience in our country. We like to report the clinical outcome of diffuse coronary artery disease with overlapping stents in our hospital. Methods: From September 2007 to October 2011, we evaluated 241 consecutive patients who required overlapping stents for diffuse coronary artery disease (>40 mm). A retrospective review was conducted to see in-hospital, short term 1 to 9 months and beyond 9 months clinical outcome. Those who presented with acute myocardial infarction or in cardiogenic shock, resuscitated and intubated before the procedure were excluded from the study. Results: The study population consists of 241 patients out of which 91.7% were male, minimum age was 31 years and maximum 82 years (53.69 ± 10.96). Among coronary artery risk factor 59.6% were diabetic, 59.8% were hypertensive, 47.3% were dyslipidaemic, 29.9% were smokers, and 28.8% with positive family history of coronary artery disease. The number of stents implanted per patient was 2.26 and mean total length was 56.44 ± 12.56. One patient had in-hospital stent thrombosis, 5 patients had in-stent restenosis, and 8 patients died during follow-up. One hundred and eighty-two (75.5%) patients completed minimum 9 months clinical follow-up. Forty patients underwent relook CAG (conventional or CT-CAG). Among them 34 patients had patent stents and 5 patients had in-stent restenosis. Four patients (2.1%) required repeat stenting and one patient (0.04) required CABG. Overall survival was 97.90%. Conclusion: Patients with long lesion had very high risk of restenosis in the past. In these patients drug eluting stent dramatically reduce the risk of restenosis translating into a good clinical outcome. DOI: http://dx.doi.org/10.11566/cmoshmcj.v12i2.39 Chatt Maa Shi Hosp Med Coll J 2013; 12(2): 45-48